(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
The article examines the values, their classification and the impact on the results of labor. The place of values in the creation of an effective system of personnel management is determined. The role of personality in the process of personnel management is highlighted. The main features of the personality that influence its behavior are revealed: internalize, externalism, authoritarianism, Machiavelli’s, orientation towards achievement, predisposition to risk. The most important values (economic, social, aesthetic, theoretical, religious, political) that form the behavior of a person in an organization are determined. It was established that the primary determinants of human behavior and its outcome are personal qualities of a person, environment, interests, guidelines, human needs, social status and status, previous experience, goals, human orientation and desire to study. The most typical relations of the individual in the organization are distinguished: job satisfaction; interest in work; organizational commitment - orientation of the individual to the organization within the framework of identifying oneself with her and feeling of independence and loyalty; the search for the reduction of dissonance - an attempt to reduce the contradiction between the life position and the behavior of the individual. The emphasis is on those values that are the priority in everyday life.